Fostering refugee resilience : global perspectives on integration, inclusion, and prosperity (Emerald Publishing Limited, 2025)
Every year, millions of people are forced to leave their homes due to conflict, violence, human rights violations, discrimination, disasters, and the impact of climate change. As a result of this, refugees bring skills, talents, and aspirations to the countries they are displaced to. This edited collection offers a comprehensive exploration of the inclusion and opportunities for refugees as they integrate themselves into new societies. With contributions from a diverse range of experts and practitioners from around the world, the chapters highlight innovative initiatives, case studies, and recommendations for building more inclusive communities. The authors, coming from different parts of the world, including Colombia, Mexico, North Macedonia, India, Spain, USA, UAE, Lebanon, Nigeria, and Switzerland, bring insights into the diverse experiences and perspectives of refugees. They emphasize the talents, resilience, and potential contributions of refugees, rather than viewing refugees as passive recipients of aid. Covering not only economic and social dimensions but also ethical, spiritual, educational, cultural, and environmental considerations, Fostering Refugee Resilience emphasizes the importance of fostering inclusive environments that embrace diversity. As well as the vibrant research community, it is also dedicated to policymakers, activists, and community members seeking to support refugee integration.
Keywords: Refugees.; Social integration.; Social Science -- Refugees.; Refugees and political asylum.; elektronické knihy; electronic books